Canadian forest fires, Icelandic volcanoes and increased local dust observed in six shallow Greenland firn cores - H. A. Kjær; P. Zens; S. Black; K. H. Lund; A. Svensson; P. Vallelonga (Climate of the Past, 2022)
Greenland ice cores provide information about past climate. Few impurity records covering the past 2 decades exist from Greenland. Here we present results from six firn cores obtained during a 426 km long northern Greenland traverse made in 2015 between the NEEM and the EGRIP deep-drilling stations situated on the western side and eastern side of the Greenland ice sheet, respectively. The cores (9 to 14 m long) are analyzed for chemical impurities and cover time spans of 18 to 53 years ( ±3 years) depending on local snow accumulation that decreases from west to east. The high temporal resolution allows for annual layers and seasons to be resolved. Insoluble dust, ammonium, and calcium concentrations in the six firn cores overlap, and the seasonal cycles are also similar in timing and magnitude across sites, while peroxide (H 2 O 2 ) and conductivity both have spatial variations, H 2 O 2 driven by the accumulation pattern, and conductivity likely influenced by sea salt. Overall, we determine a rather constant dust flux over the period, but in the data from recent years (1998–2015) we identify an increase in large dust particles that we ascribe to an activation of local Greenland sources. We observe an expected increase in acidity and conductivity in the mid-1970s as a result of anthropogenic emissions, followed by a decrease due to mitigation. Several volcanic horizons identified in the conductivity and acidity records can be associated with eruptions in Iceland and in the Barents Sea region. From a composite ammonium record we obtain a robust forest fire proxy associated primarily with Canadian forest fires ( R =0.49 ).